G. M. Hopkins´ “The Windhover” as an Ambiguous Symbol - Smažilová, Petra (American & British Studies Annual, 2009)
Gerard Manley Hopkins himself called The Windhover “the best thing he ever wrote” (Peters, 81). This could be the main motive for adding “To Christ our Lord” under the title six years after the sonnet had been written. The implied ambiguities of “The Windhover,” evoking different kinds of explanation, constitute one of the reasons why it “is probably the most written about short poem in the English language” (Pick, 1). The phrase “To Christ our Lord” accompanying the title was made central to the discussion, as it was believed to form the key ambiguity that utterly influences the meaning of the whole work. This essay concentrates on the line “To Christ our Lord” and on two different approaches to and interpretations of “The Windhover.”